Development and characterization of catalyst materials from magnetic sand, Crotalaria pallida and kaolin - K.W, Shalbugau; P.M, Dass; M, Iji; I, Nkafamiya I; O. N., Maitera (International Journal of Advanced Chemistry, 2021)
In this study, magnetic sand and Crotalaria pallida gotten from Adamawa and Bauchi states of Nigeria, respectively, were mixed after treatment, and impregnated with kaolin using a wet impregnation method and the resulting material was characterized using scanning electron microcopy (SEM), X-ray fluorescence (XRF) and X-ray diffraction (XRD). The result of XRF analysis revealed the existence of a number of dopant-like constituents in the sample, which substitute parts of important atoms in the spinel structure, however, not forming individual phases. The SEM micrographs displayed pore structures with high surface area consistent with effective catalyst materials. XRD analysis confirmed crystalline phases of the hybrid material showing typical diffraction peaks of kaolinite minerals (Al2Si2O9), Muscovite (Al12FeSi12K4NaRbH16O48), quartz, Si3O6 Calcite (Ca6C6O18) and Halite (Na4Cl4) and the average crystallite size was determined to be 75.30 nm.Â Â